Pembekalan Teknis Pelayanan Online Administrasi Kependudukan Bagi Relawan Milenial Melawan Pandemi Covid 19 - Ranggi Praharaningtyas Aji; Retno Waluyo; Fiby Nur Afiana; Ito Setiawan (Madani : Indonesian Journal of Civil Society, 2020)
Coronavirus pandemic in Indonesia has not subsided yet. There are around 100,303 cases suspected to coronavirus during the five months outbreak. in order to deal with the epidemic, volunteers are needed to help media personnel to prevent the transmission of COVID-19 virus. it is done not only by distributing masks or spraying disinfectant but also by preventing the community from gathering at the public administration services. as a millennial volunteer who understands technology, we try to provide an understanding of the public regarding the administration of online documents. the purpose of this activity is to share knowledge to COVID-19 volunteers while taking care of population data such an e-KTP, birth certificates, and others because it can be done by accessing the DINDUKCAPIL Banyumas website. it is implemented by making presentations and exposure through video conferences via the Cisco Webex Meeting application. the result is the volunteers understand how to handle the population of the online document so that they can share it with their community.